The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.17533/udea.vitae.v23n1a06
|View full text |Cite
|
Sign up to set email alerts
|

Consumer practices for purchase, storage, and preparation of poultry and eggs in selected north and south american countries: a pilot study

Abstract: Background: Poultry, eggs, and their products represent a potential food safety hazard. Although consumer practices related to these foods have been studied in various countries, little data exists from Latin America. Objective: The objective of this pilot study was to provide initial data to characterize consumers' purchase, storage, handling, and preparation of poultry products and eggs in three countries: Argentina, Colombia, and USA. Methods: Consumers (n = 425 total) in each location completed a questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Opened food containers such as canned tomatoes and fruits are store in refrigerator stores (mean= 1.21, CV= 0.33). This statement in contrast with Koppel (2016), who found that open cans can't store in the refrigerator because chemicals, particularly acidic food such as fruit and tomatoes, can be polluted. 8.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Opened food containers such as canned tomatoes and fruits are store in refrigerator stores (mean= 1.21, CV= 0.33). This statement in contrast with Koppel (2016), who found that open cans can't store in the refrigerator because chemicals, particularly acidic food such as fruit and tomatoes, can be polluted. 8.…”
Section: Resultsmentioning
confidence: 77%
“…Raw meat is stores on the first shelf in the refrigerator store (mean=1.61, CV=30%). According to Koppel (2016), to avoid crosscontamination, raw meats could always is kept at the bottom of the refrigerator. 9.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of consumers buying eggs in markets varies, ranging from 1.1% in Italy to 48% in Argentina (Koppel et al., 2016). According to Parker (2013), local farmers’ markets are becoming more attractive to consumers.…”
Section: Consumer Food Journey: Where and How Risk May Occurmentioning
confidence: 99%
“…Many researchers have investigated the effects of incorrect temperature in a cold chain on perishable foods, such as fresh pork and poultry (Bruckner et al, 2012), sliced ham (Derens-Bertheau et al, 2015), and vacuum-packed pork ham slices (Geczi et al, 2017). Koppel et al (2014Koppel et al ( , 2015Koppel et al ( , 2016 surveyed consumers' egg purchase, storage, and preparation behaviors in selected countries. Koppel et al (2016) indicated that almost all US consumers purchased chilled eggs and stored them in a refrigerator.…”
Section: Introductionmentioning
confidence: 99%